Niveles de corte y su efecto en las características agronómicas y rendimiento de forraje de Moringa oleífera "moringa" en Loreto, Perú - 2021 - Ticlavilca Chanchari, Alejandro Antony (2022)
The research was carried out in the city of Iquitos at the National University of the Peruvian Amazon. Faculty of Agronomy, located in the community of Zungarococha, whose title is CUTTING LEVELS AND ITS EFFECT ON THE AGRONOMIC CHARACTERISTICS AND FORAGE YIELD OF Moringa oleifera “MORINGA” IN LORETO, PERU- 2021. The evaluation was carried out at 60 days of planting in the final field, the experimental units have 3.6 square meters and there are 24 of them, the design used is a DBCA (random complete block design), with 4 treatments and 6 repetitions and the treatments are: observes that the best yields occurred in the T3 treatment (60% biofertilizer and 40% water), in plant height with 146 cm, coverage with 92%, green matter with 3.10 kg/m2 and dry matter with 0.65 kg/m2. m2. That the best green matter yield achieved per hectare is 31,000 kilos and the lowest green matter yield was 18,200 kilos at 63 days of cutting, it occurred with the concentration of 60% and 20% of liquid biofertilizer. That, at a higher concentration of foliar biofertilizer, the response of the forage Tithonia diversifolia "Button of gold" at 63 days, increases following a growing linear response.